Effects of hypergravity on the photosynthetic flagellate, Euglena gracilis - Lebert, M (Journal of plant physiology, 1997)
Euglena gracilis, a unicellular, photosynthetic flagellate, orients itself by means of gravi- and phototaxis to reach and stay in regions optimal for survival and growth. An improved version of the slow rotating centrifuge microscope, NIZEMI, was used to test wild type and mutant strains for their responses to hypergravity. Wild type cells could actively move against the acceleration vector up to 8.5 gn and were centrifuged down at higher rates. Even at 10.5 gn, the highest value tested, cells were still negative gravitactically oriented as shown by video images. In contrast, all mutant strains as well as Astasia longa, a close relative of Euglena, could move against the acceleration vector under all conditions tested. With increasing accelerations the mean orientation of the populations shifted according to a vectorial addition of gravity and acceleration. The r-value, a statistical measure of the orientation of a population, increased with moderately increased acceleration rates and decreased at higher values. While wild type Euglena and two of the three mutant strains tested were exclusively negative gravitactically, in the third strain as well as in Astasia longa half of the population reacted negative gravitactically and the other half positive gravitactically. This variation of the wild type behavior was observed at moderate acceleration rates. At high accelerations the cells became exclusively positive gravitactic. The obtained results are discussed on the basis of the current model explaining gravitaxis